Do caregivers' personality and emotional intelligence modify their perception of relationship and communication with people with aphasia?. Issue 5 (18th June 2020) - Kroll, Aleksandra; Karakiewicz, Beata
Abstract: Background: There is a wide agreement that family and friends of people with aphasia (PWA) can play a crucial role in the rehabilitation of interpersonal communication. Therefore, speech and language therapists (SLTs) should include family and friends in the process of therapy. However, little has been said about the role of caregivers of severely disabled PWA in the rehabilitation of communication functions. Aims: To examine how caregivers of severely disabled PWA perceive their relationship and communication with PWA, how they facilitate communication with PWA, and whether the caregiver's personality and emotional intelligence modify the abovementioned processes. Methods & Procedures: The study involved 123 caregivers of severely disabled stroke survivors with aphasia. Participants took part in a structured interview based on a structured interview guide created for the purpose of this study. The standardized psychological questionnaires NEO Five‐Factor Inventory (NEO‐FFI) and Schutte Emotional Intelligence Scale (SEIS) were used. Outcomes & Results: The caregiver's positive attitude towards the PWA correlated with the active facilitation of communication. The personality traits of caregivers and their level of emotional intelligence were associated with the tendency to use certain techniques to facilitate communication with PWA. Conclusions & Implications: Caregivers' positive attitude towards PWA is beneficial for the rehabilitation of communicative functions. Personality traits and emotional intelligence could modify the caregiver's strategy of coping with aphasia‐related challenges and should be taken into consideration when providing support. What this paper adds: What is already known on the subject: Interpersonal communication must by definition involve at least two people. Therefore, there are a lot of approaches in SLT where support is given not only to the PWA but also to the communication partners. The most important group is significant others, which is usually understood as family members and friends. There is an increasing recognition that SLTs should include them in therapy. What this paper adds to existing knowledge: For those PWA who need constant care, caregivers may have a significant influence on the quality of communication. Their positive attitude towards PWA corresponds with more active facilitation of communication and can make rehabilitation more efficacious. Caregivers should be educated on the cognitive and behavioural aspects of aphasia and encouraged to look actively for a PWA's positive characteristics. Caregivers' personality traits play a role in facilitating communication. For example, caregivers with high agreeableness are more likely to enjoy providing care, while those with higher conscientiousness declare using more techniques to facilitate communication with the PWA. What are the potential or actual clinical implications of this work?: Caregivers' personality traits play a role in caring. Their positive attitude towards PWA corresponds to more active facilitation of communication, which can lead to more effective rehabilitation. This should be taken into account when training caregivers. Training programmes should include cognitive and behavioural aspects of aphasia as well as emphasize the need to maximize the PWA's abilities.